The choice of an optimal graft for the superior capsule reconstruction of the shoulder with a massive rotator cuff tear - Daria A. Naida (Eco-vector, 2021)
Background: The study hypothesis is that the knowledge about the mechanical properties of biological tissues will help surgeons to choose a transplant.